(untitled) (Revista Apotheke, 2025)
This article investigates how urban perception can be enriched by sketches made on site, expanding the sensory experience beyond vision and including senses such as smell, touch and hearing. It explores how the human body perceives the urban environment and how affections influence the drawing process. The objective is to analyze how these sensory stimuli impact the creation of sketches by Architecture and Urban Planning students with the following question: How does sensory perception influence designers’ sketches of the city? The research adopts a qualitative methodology, collecting testimonies and sketches from students in observation and drawing activities on site and makes a psychogeographic analysis of the data. The theoretical foundation is based on authors such as Spinoza, who discusses the influence of affections on bodies, Baudelaire, with his concept of flâneur as urban observer, and Juhani Pallasmaa, who emphasizes the importance of the senses in architectural perception, to understand the interactions between body, city and the practice of location drawing.